Exposure to cholinesterase inhibiting insecticides and blood glucose level in a population of Ugandan smallholder farmers. (6th July 2020) - Hansen, Martin Rune Hassan; Jørs, Erik; Sandbæk, Annelli; Sekabojja, Daniel; Ssempebwa, John C; Mubeezi, Ruth; Staudacher, Philipp; Fuhrimann, Samuel; Burdorf, Alex; Bibby, Bo Martin; Schlünssen, Vivi
Abstract : Objectives: The risk of diabetes mellitus may be elevated among persons exposed to some pesticides, including cholinesterase-inhibiting insecticides (organophosphates and carbamates). The objective of this study was to investigate how acetylcholinesterase activity was associated with mean blood glucose levels among smallholder farmers in Uganda. Methods: We conducted a short-term follow-up study among 364 smallholder farmers in Uganda. Participants were examined three times from September 2018 to February 2019. At each visit, we measured glycosylated haemoglobin A (HbA1c ) as a measure of long-term average blood glucose levels. Exposure to organophosphate and carbamate insecticides was quantified using erythrocyte acetylcholinesterase normalised by haemoglobin (AChE/Hb). For a subgroup of participants, fasting plasma glucose (FPG) was also available. We analysed HbA1c and FPG versus AChE/Hb in linear mixed and fixed effect models adjusting for age, sex, physical activity level, and consumption of fruits and vegetables, alcohol and tobacco. Results: Contrary to our hypothesis, our mixed effect models showed significant correlation between low AChE/Hb and low HbA1c . Adjusted mean HbA1c was 0.74 (95% CI 0.17 to 1.31) mmol/mol lower for subjects with AChE/Hb=24.3 U/g (35th percentile) compared with subjects with AChE/Hb=25.8 U/g (50th percentile). Similar results were demonstrated for FPG. Fixed effect models showed less clear correlations for between-phase changes in AChE/Hb and HbA1c . Conclusions: Our results do not clearly support a causal link between exposure to cholinesterase-inhibiting insecticides and elevated blood glucose levels (expressed as HbA1c and FPG), but results should be interpreted with caution due to the risk of reverse causality.